Regulation of Ace2-dependent genes requires components of the PBF complex in Schizosaccharomyces pombe - Suárez, M Belén (Cell Cycle, 2015)
The division cycle of unicellular yeasts is completed with the activation of a cell separation program that results in the dissolution of the septum assembled during cytokinesis between the 2 daughter cells, allowing them to become independent entities. Expression of the eng1(+) and agn1(+) genes, encoding the hydrolytic enzymes responsible for septum degradation, is activated at the end of each cell cycle by the transcription factor Ace2. Periodic ace2(+) expression is regulated by the transcriptional complex PBF (PCB Binding Factor), composed of the forkhead-like proteins Sep1 and Fkh2 and the MADS box-like protein Mbx1. In this report, we show that Ace2-dependent genes contain several combinations of motifs for Ace2 and PBF binding in their promoters. Thus, Ace2, Fkh2 and Sep1 were found to bind in vivo to the eng1(+) promoter. Ace2 binding was coincident with maximum level of eng1(+) expression, whereas Fkh2 binding was maximal when mRNA levels were low, supporting the notion that they play opposing roles. In addition, we found that the expression of eng1(+) and agn1(+) was differentially affected by mutations in PBF components. Interestingly, agn1(+) was a major target of Mbx1, since its ectopic expression resulted in the suppression of Mbx1 deletion phenotypes. Our results reveal a complex regulation system through which the transcription factors Ace2, Fkh2, Sep1 and Mbx1 in combination control the expression of the genes involved in separation at the end of the cell division cycle.